2013
DOI: 10.1073/pnas.1307096110
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of mitochondria-targeted antioxidants in an acute bacterial infection

Abstract: Acute pyelonephritis is a potentially life-threatening infection of the upper urinary tract. Inflammatory response and the accompanying oxidative stress can contribute to kidney tissue damage, resulting in infection-induced intoxication that can become fatal in the absence of antibiotic therapy. Here, we show that pyelonephritis was associated with oxidative stress and renal cell death. Oxidative stress observed in pyelonephritic kidney was accompanied by a reduced level of mitochondrial B-cell lymphoma 2 (Bcl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 59 publications
(51 reference statements)
3
56
0
Order By: Relevance
“…Cytoprotection related to reduction of mitochondrial ROS has already been reported for several drugs (Reddy, 2006;Szeto, 2006;Plotnikov et al, 2013) and a mitochondrial-targeted antioxidant has recently been shown to be beneficial in reducing intestinal epithelial barrier dysfunction (Wang et al, 2014). Upregulation of SOD-2 expression by resveratrol together with an increase in cellular reduced glutathione (GSH) level was also reported in human coronary arterial endothelial cells; the compound also attenuated mitochondrial O 2  production induced by a high glucose concentration; these effects were mediated by activation of the protein deacetylase silent mating-type information regulation 2 homologue (sirtuin) 1 (SIRT1) (Ungvari et al, 2009).…”
Section: Ros Contributes To Its Anti-apoptotic/cytoprotective Effectsmentioning
confidence: 90%
“…Cytoprotection related to reduction of mitochondrial ROS has already been reported for several drugs (Reddy, 2006;Szeto, 2006;Plotnikov et al, 2013) and a mitochondrial-targeted antioxidant has recently been shown to be beneficial in reducing intestinal epithelial barrier dysfunction (Wang et al, 2014). Upregulation of SOD-2 expression by resveratrol together with an increase in cellular reduced glutathione (GSH) level was also reported in human coronary arterial endothelial cells; the compound also attenuated mitochondrial O 2  production induced by a high glucose concentration; these effects were mediated by activation of the protein deacetylase silent mating-type information regulation 2 homologue (sirtuin) 1 (SIRT1) (Ungvari et al, 2009).…”
Section: Ros Contributes To Its Anti-apoptotic/cytoprotective Effectsmentioning
confidence: 90%
“…APOSTOLOVA AND VICTOR inhibited leukocyte infiltration in the kidney and the spreading of the inflammatory process (242). SkQR1 recovered normal ROS levels in the leukocytes and expression of Bcl-2 in the kidney of pyelonephritic rats.…”
mentioning
confidence: 90%
“…In vitro models of hemolysis (226) Kidney function in myoglobinuria (rhabdomyolysis) or ischemia/reperfusion rat model (241) Rat model (242) damage (294). In short, in isolated mitochondria, MitoQ seems to fulfill most of the requirements of a successful mitochondriatargeted antioxidant.…”
Section: Skq1 Skqr1mentioning
confidence: 99%
“…In the current study, we used SkQ1 antioxidant, based on the plastoquinone moiety linked to dodecyltriphenylphosphonium cation that targets SkQ1 to mitochondria [26]. SkQ1 and its analogs are efficient in the prevention of some age-associated pathologies, and they have therapeutic effects in animal models of diseases associated with inflammatory response (heart, brain, and kidney ischemic injury [27, 28], pyelonephritis [29], eye diseases [30, 31], sarcopenia [32], and dermal wound healing [33]). SkQ1 delays the development of various markers of aging and prolongs the lifespan of various animals [20, 22, 34, 35].…”
Section: Introductionmentioning
confidence: 99%